2008
DOI: 10.1111/j.1601-183x.2008.00410.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic susceptibility to heroin addiction: a candidate gene association study

Abstract: Heroin addiction is a chronic complex disease with a substantial genetic contribution. This study was designed to identify genetic variants that are associated with susceptibility to develop heroin addiction by analyzing 1350 variants in 130 candidate genes. All subjects had Caucasian ancestry. The sample consisted of 412 former severe heroin addicts in methadone treatment, and 184 healthy controls with no history of drug abuse. Nine variants, in six genes, showed the lowest nominal P values in the association… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
232
2
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(262 citation statements)
references
References 76 publications
(78 reference statements)
23
232
2
4
Order By: Relevance
“…Additionally, the CSNK1E SNP rs1534891 was associated with heroin addiction (Levran et al, 2008). Furthermore, coadministration of the casein kinase 1-d (Csnk1d)-preferring inhibitor PF-670462 with MA decreased locomotor activity and DARPP-32 phosphorylation in mice (Bryant et al, 2009b), and a similar result was observed following coadministration of PF-670462 with amphetamine in rats (Li et al, 2011).…”
Section: Introductionsupporting
confidence: 62%
See 1 more Smart Citation
“…Additionally, the CSNK1E SNP rs1534891 was associated with heroin addiction (Levran et al, 2008). Furthermore, coadministration of the casein kinase 1-d (Csnk1d)-preferring inhibitor PF-670462 with MA decreased locomotor activity and DARPP-32 phosphorylation in mice (Bryant et al, 2009b), and a similar result was observed following coadministration of PF-670462 with amphetamine in rats (Li et al, 2011).…”
Section: Introductionsupporting
confidence: 62%
“…Interestingly, we recently replicated the association of the CSNK1E SNP rs135745 with amphetamine-induced subjective euphoria (Veenstra-VanderWeele et al 2006) in healthy human volunteers in a new cohort of 282 subjects (Amy et al, unpublished data). The Csnk1e locus also affected opioid sensitivity (Figure 3) which, along with a previous association between a SNP in CSNK1E and heroin dependence (Levran et al, 2008), further implicates Csnk1e as a genetic regulator of sensitivity to drugs of abuse. Of particular note, a nearly identical genetic locus that we have identified (77)(78)(79)(80)(81)(82)(83) Mb in the present study) also regulates alcohol consumption in mice .…”
Section: Discussionmentioning
confidence: 94%
“…Thus, galanin interacts with 5-HT1A receptors, and galanin antagonists and agonists have anxiolytic and antidepressive effects in animal experiments (144)(145)(146)(147)(148)(149)(150)(151). Interestingly, association of genes encoding galanin and/or GalR3 has been reported for psychiatric phenotypes (152)(153)(154), including panic disorder (155), depression-related parameters (156)(157)(158), and nicotine dependence (159,160).…”
Section: Significancementioning
confidence: 99%
“…previous genetic studies on humans that the galanin system is involved in psychiatric disorders including alcoholism/addiction (43)(44)(45)(46)(47), panic disorder (48,49), and chronic pain-associated depression (50). Furthermore, recent functional studies provided the first evidence that polymorphisms in a highly conserved genetic region upstream from the GAL gene regulates GAL expression in brain areas, such as the amygdala and hypothalamus, implicated in the pathogenesis of depression (51,52).…”
mentioning
confidence: 99%